Explaining the Persistent Effect of the Euro-Changeover on German Restaurant Prices - Thomas A. Eife (University of Heidelberg, Department of Economics, 2011)
This paper studies the long-run effect of the 2002 changeover on restaurant prices in Germany. German restaurant prices increased significantly when the euro was introduced as a new currency but rather than returning to their re-changeover trend, restaurant prices appear to have stabilized on a higher path. This stands in contrast to the prediction of menu costs models or models of confusion-induced price increases as these models can only account for a transitory effect. The persistence of the increase suggests the existence of more than one price equilibrium. This multiplicity of price equilibria is a central part of the explanation proposed in the paper.
urn:nbn:de:bsz:16-opus-125678
Keywords: D43; E31; L13; L89; 330; Gastronomie; Preis; Hysterese; Währungsumstellung; Euro; Gleichgewichtsmodell; Deutschland